2015
DOI: 10.1097/mib.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-coupled pH-sensing Receptor OGR1 Is a Regulator of Intestinal Inflammation

Abstract: Article first published online 7 April 2015.Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
100
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(115 citation statements)
references
References 59 publications
14
100
1
Order By: Relevance
“…Our earlier work has shown that OGR1 mRNA is expressed in human small intestine and colon (6). We notably observed that OGR1 expression is significantly higher in human colon biopsies from CD and UC patient groups compared with the non-IBD control group.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Our earlier work has shown that OGR1 mRNA is expressed in human small intestine and colon (6). We notably observed that OGR1 expression is significantly higher in human colon biopsies from CD and UC patient groups compared with the non-IBD control group.…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, it is expected that chronic activation of OGR1 may exacerbate tissue damage in IBD, which may be sustained further by increased release of inflammatory mediators from myeloid cells exposed to acidic pH (6). Indeed, we could show that deficiency of OGR1 protects female mice from disease manifestations in a murine model of IBD (6).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Ovarian cancer G protein-coupled receptor 1 (OGR1) has recently been implicated as a regulator of intestinal inflammation through the control of macrophage inflammatory responses [69]. Using IL-10 −/− (knockout) mice for the development of chronic spontaneous intestinal inflammation, OGR1 deficiency alleviated mucosal inflammation when compared to control mice.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of pH on the two biological processes may constitute a balancing act integrating adaptation to the environment as well as sexual reproduction. Because in mammals, pH or proton sensing GPCRs were discovered (Tomura et al, 2005;de Valliere et al, 2015), and the use of receptors of the GPCR family for sensing environmental cues is conserved among eukaryotes; it is likely that fungi exploit similar mechanisms. In this context, it would be interesting to investigate the involvement of fungal GPCRs, such as Ste2 in S. cerevisiae (Kim et al, 2012), in pH sensing and adaptation mechanisms.…”
Section: Sensing Of Physical Cuesmentioning
confidence: 99%